HASIL UJI KELAYAKAN KASUS GIZI BURUK SEBAGAI INDIKATOR KEJADIAN LUAR BIASA KURANG PANGAN DI MASYARAKAT - Syarifudin Latinulu; Vita Kartika; Basuki Budiman (Persagi, 2000)
RESULTS FROM FEASIBILITY STUDY ON THE SEVERE MALNOURISHED CASES AS AN INDICATOR OF OUTBREAK OF FOOD SHORTAGES IN THE COMMUNITY.Background: Outbreak of marasmus, kwashiorkor, and Marasmic-kwashiorkor on children underfive years old in Indonesia have been reported on the late of 1998. Those cases assumed as the impact of economic crises since the middle of 1997's. It was stated by the Ministry of Health that if there is a malnourish child found in one area, the people on the surrounded have been suffer from a lack of food. Objective: The Feasiblity study on cases of marasmus and/or kwashiorkor as an indcator of outbreak of a lack of food consumption in the area surrounding was carried out in the District of Bandung, Cirebon, Karawang, and Cianjur, West Java, 1999.Method: 66 villages were chosen purposively based on a present of marasmus and/or kwashiorkor in that areas according to the result of sweeping to the all areas and month-weighing program (Mei-June 1999). There were 81 children identified suffer from Marasmus/Kwashiorkor/Marasmic-Kwashiorkor. Of the 81 cases in 66 villages confirmed were found 56 marasmus, 4 kwashiorkor, 9 marasmic-kwashiorkor, 12 severe degree of malnutrition, and 4 children was passed out without clinical symptom/signs. The main data collected were M, K, and MK, nutritional status data in Posyandu, and social economic status of the household sample of the poor surrounding the cases, and food consumption of the household samples.Results: The results were 16 villages (30,7%) as the malnourished villages, although no consumption pattern changes. Marasmus, Kwashiorkor, or Marasmic-Kwashiorkor no longer used as an indicator of a lack of food consumption in the areas. These because (a) Marasmus and kwashiorkor already happened long-time before the outbreak cases reported, (b) Some of marasmic or kwashiorkor children not belong to the poor community. 72,5 % cases were belong to the children below two years old, and the largest belongs to children below 18 months old.Key Words: nutritional outbreak, marasmus, kwashiorkor, food consumption of the poor